Interpretação psicanalítica e criação literária: “A cabeça da Medusa” de Freud - Lima, Graziele Gonçalves de (Universidade Federal de São Carlos, 2020)
The Medusa’s Head is a posthumous article published in 1940, although it was written in 1922. In this manuscript, Freud performs the psychoanalytical interpretation of a mythological symbol. It is possible to find other mentions about Medusa in published articles, for example, some aspects are pointed out in The Infantile Genital Organization (1923) when Freud examines the “sexual difference”, the figure also appears in the 29th conference: Review of the theory of the dream (1933). Freud, by commenting on some images that are frequently present in dreams that express the fear of castration, places the mythological figure of Medusa's head as one of the representations of this dread. In this dissertation we seek to discuss The Medusa’s Head (1922 [1940]), supporting us in some reinterpretations of the myth to elucidate, from the technical point of view, how it is possible to carry out the interpretation of a mythological narrative. The investigation was divided into the following segments: Literary creation and its relationship with fantasy; the uncanny in the literature and in the head of Medusa and the development of child sexuality. As a final part, we highlight Medusa's figurations, especially the strong association between feminine and horror. We conclude that considering Freud's statement that the artist has access to the laws of psychic processes and manages them to transmit on his works something of his unconscious fantasies, with myths, literature, and art, we can have access to a symbolism that for the subject is full of meaning.
Psychoanalytic interpretation and literary creation: "Medusa's head” by Freud
Keywords: Psicanálise freudiana; Cabeça da Medusa; Interpretação psicanalítica; Freudian psychoanalysis; Medusa´s head; Psychoanalytic interpretation; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA